מהו הצורה הסטנדרטית של y = (2 + x ^ 2) (x-7) - (2x + 3) ^ 2?

מהו הצורה הסטנדרטית של y = (2 + x ^ 2) (x-7) - (2x + 3) ^ 2?
Anonim

תשובה:

# x ^ 3 - 11x ^ 2 - 10x -23 #

הסבר:

הדבר הראשון לעשות הוא להכפיל את זוגות בסוגריים

# (2 + x ^ 2) (x - 7) # = # 2 (x - 7) + x ^ 2 (x - 7) # # =# 2x - 14 + x ^ 3 - 7x ^ 2 #

ו (2x + 3) = 2x (3x + 3) + 3 (2x + 3)

= # 4x ^ 2 + 6x + 6x + 9 #

הביטוי הופך עכשיו

# 2x - 14 + x ^ 3 - 7x ^ 2 - (4x ^ 2 + 12x 9) # #

# = 2x - 14 + x ^ 3 - 7x ^ 2 - 4x ^ 2 - 12x - 9 #

# = x ^ 3 -11x ^ 2 - 10x -23 #